Recoup From Home? Comparison of Relative Cost Savings for ACDF, Lumbar Discectomy, and Short Segment Fusion Performed in the Inpatient Versus Outpatient Setting. Issue 1 (April 2021) - Mikhail, Christopher M.; Echt, Murray; Selverian, Stephen R.; Cho, Samuel K.
Study Design: Broad narrative review. Objective: To review and summarize the current literature on the cost efficacy of performing ACDF, lumbar discectomy and short segment fusions of the lumbar spine performed in the outpatient setting. Methods: A thorough review of peer- reviewed literature was performed on the relative cost-savings, as well as guidelines, outcomes, and indications for successfully implementing outpatient protocols for routine spine procedures. Results: Primary elective 1-2 level ACDF can be safely performed in most patient populations with a higher patient satisfaction rate and no significant difference in 90-day reoperations and readmission rates, and a savings of 4000 to 41 305 USD per case. Lumbar discectomy performed through minimally invasive techniques has decreased recovery times with similar patient outcomes to open procedures. Performing lumbar microdiscectomy in the outpatient setting is safe, cheaper by as much as 12 934 USD per case and has better or equivalent outcomes to their inpatient counterparts. Unlike ACDF and lumbar microdiscectomy, short segment fusions are rarely performed in ASCs. However, with the advent of minimally invasive techniques paired with improved pain control, same-day discharge after lumbar fusion has limited clinical data but appears to have potential cost-savings up to 65-70% by reducing admissions. Conclusion: Performing ACDF, lumbar discectomy and short segment fusions in the outpatient setting is a safe and effective way of reducing cost in select patient populations.